Bernard Shaw and the Making of Modern Ireland
XXVI, 274 p.
Keywords: This book is an anthology focused on Shaw’s efforts, literary and political, that worked toward a modernizing Ireland. Following Declan Kiberd’s Foreword and the editor’s Introduction, the contributing chapters, in their order of appearance, are from President of Ireland Michael D. Higgins, Anthony Roche, David Clare, Elizabeth Mannion, Nelson O’Ceallaigh Ritschel, Aisling Smith, Susanne Colleary, Audrey McNamara, Aileen R. Ruane, Peter Gahan, and Gustavo A. Rodriguez Martin. The essays establish that Shaw’s Irishness was inherent and manifested itself in his work, demonstrating that Ireland was a recurring feature in his considerations. Locating Shaw within the march towards modernizing Ireland furthers the recent efforts to secure Shaw’s place within the Irish spheres of literature and politics. .